2021
DOI: 10.3389/fnagi.2021.729635
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Brain-Predicted Age in Amnestic and Non-amnestic Sporadic Early-Onset Alzheimer's Disease

Abstract: Objective: Predicted age difference (PAD) is a score computed by subtracting chronological age from “brain” age, which is estimated using neuroimaging data. The goal of this study was to evaluate the PAD as a marker of phenotypic heterogeneity and severity among early-onset Alzheimer's disease (EOAD) patients.Methods: We first used 3D T1-weighted (3D-T1) magnetic resonance images (MRI) of 3,227 healthy subjects aged between 18 and 85 years to train, optimize, and evaluate the brain age model. A total of 123 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…However, individual anatomical and physiological differences together with the uncertainty of the MRI measurements set a limit on the theoretically achievable prediction accuracy; and at some point, it becomes questionable if a lower MAE is desirable—because instrumental variability is removed—or if even higher MAE can improve brain age's performance in disease—because meaningful physiological variability is added. Within‐subject longitudinal brain age changes, as a proxy for brain age repeatability, assuming the intra‐individual ageing is negligible compared with the inter‐individual age differences, take the inter‐individual variations out of the equation and might therefore achieve more accurate predictions of age changes across time both for healthy participants, and have accrued interest lately (Aamodt et al, 2022 ; Franke & Gaser, 2019 ; Gautherot et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, individual anatomical and physiological differences together with the uncertainty of the MRI measurements set a limit on the theoretically achievable prediction accuracy; and at some point, it becomes questionable if a lower MAE is desirable—because instrumental variability is removed—or if even higher MAE can improve brain age's performance in disease—because meaningful physiological variability is added. Within‐subject longitudinal brain age changes, as a proxy for brain age repeatability, assuming the intra‐individual ageing is negligible compared with the inter‐individual age differences, take the inter‐individual variations out of the equation and might therefore achieve more accurate predictions of age changes across time both for healthy participants, and have accrued interest lately (Aamodt et al, 2022 ; Franke & Gaser, 2019 ; Gautherot et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with SSVD exhibit high heterogeneity in imaging characteristics; as a result, cognition-related imaging differences at the group-level are difficult for use as biomarkers at the individual level. Previous studies have indicated that brain age prediction can determine brain aging based on individual brain MRI data, which can be used as an effective biomarker to estimate cognitive impairment in neurological and psychiatric disorders ( Liem et al, 2017 ; Shahab et al, 2019 ; Beheshti et al, 2020 ; Gautherot et al, 2021 ; Mishra et al, 2021 ). Thus, it is essential to investigate the association of SVCI with individual brain age.…”
Section: Introductionmentioning
confidence: 99%
“…“Predicted age difference” (PAD) calculated using deep learning techniques and magnetic resonance imaging (MRI) also demonstrated differences in the typical and nonamnestic young-onset AD. Gautherot et al [46 ▪ ] found different regional atrophy in these two groups, with the nonamnestic group having more severe neocortical and basal nuclei atrophy, leading to a higher PAD score, which was able to separate these two subtypes of AD.…”
Section: Biomarkersmentioning
confidence: 99%